Intra-Industry Trade and Input Demand - Kurt Kratena (Austrian Institute of Economic Research (WIFO), 2004)
This paper presents a static CGE model of intra-industry trade differentiating between final and intermediate goods. It makes use of the detailed information about the distribution of imports among demand categories available in input - output tables. Final goods trade and trade in intermediate goods are shown to have different economic impacts. Intermediate goods trade is the consequence of input substitution of firms causing a factor as well as a cost saving effect. Final goods trade is the consequence of product substitution of consumers and increases consumers' welfare. Results for skilled and unskilled labour and for production patterns of both types of intra-industry trade are quantified in a model version with and without full employment assumptions.
Keywords: F16; F17; D5; 330; intermediate trade; input demand; CGE modelling; Intraindustrieller Handel; CGE-Modell